The effect of perceived benefits, trust, quality, brand awareness/associations and brand loyalty on internet banking brand equity - Loureiro, S. M. C. (2017)
This research examines the interrelationships of trust, brand awareness/associations, perceived quality and brand loyalty in building Internet banking brand equity. The model was based on data from customers using online banking (customers of an international bank) using the PLS technique. The results suggest that perceived quality and brand loyalty are more important to explain the Internet banking brand equity than brand awareness/associations and trust. Interestingly, trust contributes only indirectly, through perceived quality and brand awareness/association to Internet banking brand equity. Online perceived benefits impact positively on customers' trust and online perceived risks tend to be lower when trust increases.